RADEC Model in Dance Learning to Improve Student Learning Outcomes - Nadia Zahratunnisa; juju masunah; Beben Barnas (Journal of Dance and Dance Education Studies, 2025)
The importance of learning outcomes that are the target of learning in cognitive, affective, and psychomotor aspects. Learning outcomes are one of the abilities possessed by students after receiving learning experiences that will result in changes in behavior. However, student learning outcomes in dance learning in cognitive, affective, and psychomotor aspects in class VIII-B of SMP Laboratorium Perpilot UPI Bandung are low. The purpose of this study is to improve student learning outcomes using the RADEC learning model. This study uses the Classroom Action Method (CAR) with a quantitative approach. This CAR adapts the Kemmis and Mc.Taggart model, each cycle of which consists of four stages, namely planning, implementation, observation, and reflection. This study was conducted in three cycles. The participants in this study were 21 students in class VIII-B. Data collection techniques were carried out by means of observation, testing, reflection, and literature studies. Data analysis was carried out descriptively quantitatively by calculating the average class value. The results of this study indicate that the application of the RADEC learning model increased the average value of 6 students who completed (29%) who achieved a score of 63 in the initial condition to 21 students (100%) completed with a score of 94 in the third cycle. These results indicate an increase in student learning outcomes in dance learning from the initial condition that did not use the learning model and then changed to using the RADEC learning model.